Scientific progress and internal medicine - Federspil, Giovanni; Vettor, Roberto (Medicina e Morale, 1997)
Talking about scientific progress and medicine may seem superfluous because by now the idea that scientific progress is the cause of the improvement in medical care is so widespread and deep rooted that it does not seem to leave room for doubt. However the authors believe that it is useful to point out how the relationships between scientific progress and internal medicine are more complex than they appear at first sight. Through a historical analysis of this binomial, the authors are able to show that today the specialist in internal medicine is no longer the one who, like at the end of the nineteenth century, deals with the most important problems, but he is the physician who, faced with the flood of concepts, theories, techniques and new approaches, proposed every day by scientific progress, knows how to maintain a critical and balanced mental attitude. The functions and importance of the specialist in internal medicine do not lie in knowing how to practice one or another technique or in having full knowledge of the most recent variant of every pathogenetic theory concerning a particular disease, but apart from a sufficiently broad culture, they consist in great methodological awareness and a critical attitude.